Optimization of the protein product formulation based on safflower production waste - Tultabayev Mukhtar; Zhumanova Dametken (BIO Web of Conferences, 2023)
The global volume of feed production is growing annually, for example, in 2021 it increased by 2.3%, to about 1.2 billion tons against 1.19 billion tons in 2020. The production of compound feeds is a complex technological process that allows you to obtain a final feed product with the required characteristics from several types of raw materials. The effectiveness of the finished feed depends on its chemical composition, nutritional value, form of release, etc. Each type of feed mixture is made according to a certain recipe, taking into account the type of animal or bird, breed, direction, age and contributes to the maximum disclosure of the genetic potential of an individual. The main indicator of the high quality of compound feeds is their balance in accordance with the needs of animals in irreplaceable nutrition factors. Compliance with this provision ensures a high conversion of compound feeds into livestock products. Therefore, along with the expansion of the feed base at the expense of traditional types of feed, it becomes obvious that there is a need to expand the possibilities of using non-traditional feed products, especially of plant origin. However, there is currently no effective and simple technology for recycling waste after processing oilseeds, which is an effective and simple method with significant innovative potential in the feed industry. One of the promising directions in the development of waste management technology for processing oilseeds is the use of extrusion after rational preparation of this process, which includes an even distribution of waste and valuable components.